Parental Subfertility, Fertility Treatment, and the Risk of Congenital Anorectal Malformations. Issue 2 (March 2015) - Wijers, Charlotte H.W.; van Rooij, Iris A.L.M.; Rassouli, Roxana; Wijnen, Marc H.; Broens, Paul M.A.; Sloots, Cornelius E.J.; Brunner, Han G.; de Blaauw, Ivo; Roeleveld, Nel
<x xml:space="preserve">Abstract</x> Background: Fertility treatment seems to play a role in the etiology of congenital anorectal malformations, but it is unclear whether the underlying parental subfertility, ovulation induction, or the treatment itself is involved. Therefore, we investigated the odds of anorectal malformations among children of subfertile parents who conceived with or without treatment compared with fertile parents. Methods: We performed a case-control study among 380 cases with anorectal malformations treated at 3 departments of pediatric surgery in The Netherlands and 1973 population-based controls born between August 1988 and August 2012. Parental questionnaires were used to obtain information on fertility-related issues and potential confounders. Results: In singletons, increased risks of anorectal malformations were observed for parents who underwent intracytoplasmic sperm injection (ICSI) or in vitro fertilization (IVF) treatment compared with fertile parents (odds ratio = 2.4 [95% confidence interval = 1.0–5.9] and 4.2 [1.9–8.9], respectively). For subfertile parents who conceived after IVF treatment, an elevated risk was also found when they were compared with subfertile parents who conceived without treatment (3.2 [1.4–7.2]). Among children of the latter category of parents, only the risk of anorectal malformations with other major congenital malformations was increased compared with fertile parents (2.0 [1.3–3.3]). No associations were found with intrauterine insemination or use of hormones for ovulation induction. Conclusions: We found evidence of a role of ICSI and IVF treatments in the etiology of anorectal malformations. However, subfertility without treatment increased only the risk of anorectal malformations with additional congenital malformations.